Adhesive nanostructured multilayer films using a bacterial exopolysaccharide for biomedical applications - TOKSOY ÖNER, EBRU (ROYAL SOC CHEMISTRY, 2013)
Medical adhesives and sealants often require that long-term adhesiveness is achieved. In this work, nanostructured coatings consisting of chitosan and the adhesive bacterial exopolysaccharide levan are fabricated using layer-by-layer (LbL) assembly. Taking advantage of the electrostatic self-assembly mechanism of LbL, the charges of both chitosan and a phosphonate-derivatized levan (Ph-levan) are measured and the feasibility of constructing hybrid films is monitored and confirmed using a quartz crystal microbalance with dissipation monitoring (QCM-D). The adhesive properties between two identical bonded films with a total of 100 layers are compared to control films in which Ph-levan is replaced by alginate, revealing that the detachment force of the former is about 3 times higher than the control. Scanning electron microscopy of the films surface shows that the surface of Ph-levan films is smooth and homogeneous. Cell adhesion tests were conducted using a L929 cell line. Early cell adhesion is significantly higher in chitosan/Ph-levan films when compared to chitosan/alginate controls. These findings establish levan derivatives as bioinspired ingredients for conceiving medical adhesive devices that allow achieving enhanced mechanical and biological performance.
Keywords: POLYMER-FILMS; CHITOSAN; ALGINATE; CONTACT; SYSTEMS; MECHANICS; DELIVERY; ORIGIN; TACK